Relationship of heart rate variability with serum zinc and magnesium in female rheumatoid arthritis patients - Sharmin, Afsana; Jannat, Meftahul; Sultana, Shamima; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2022)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease affecting multiple small symmetrical joints with extra-articular involvement. Altered blood mineral status is associated with the immune-inflammatory rheumatoid process. Reduced heart rate variability (HRV) is a predictor of sudden cardiac death in RA patients. So, the role of minerals for altered HRV needs investigation in RA. Objectives: To assess the relationship between HRV and serum zinc (Zn), magnesium and (Mg) levels in RA patients. Methods: This cross sectional study enrolled 60 female participants of 30-50 years of age. Among them 30 female RA patients were included in the study group and 30 age matched apparently healthy women constituted control group. Serum Zn, Mg levels were estimated by autoanalyzer and frequency domain parameters of HRV were recorded by a data acquisition device, Powerlab 8/35, AD Instruments, Australia followed by analysis with software, Lab chart. Statistical analyses were done by independent sample ‘t’ test and Pearson’s correlation coefficient test. Results: In this study, among frequency domain parameters of HRV, total power (TP), low frequency power(LF), high frequency power(HF), HF normalized unit(HF nu) were significantly lower (p<0.05) and LF normalized unit (LF nu), LF/HF ratio were significantly higher (p<0.05) in RA patients. In addition, significantly (p<0.05) lower levels of serum Zn and Mg were found in RA patients as compared to controls. But on correlation analysis, the HF nu showed significant positive correlation and LF nu and LF/HF ratio demonstrated significant negative correlation (p<0.05) with serum Mg only. Conclusion: Results of the present study revealed that low levels of serum Mg was correlated with reduced HRV in patients with RA. Moreover, low serum Mg was related to parasympathetic hypo and sympathetic hyperactivity as well as altered sympathovagal balance in RA. J Bngladesh Soc Physiol 2021;16(1): 111-117